2012
DOI: 10.1002/uog.11183
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hemodynamics at 11–13 weeks' gestation and risk of pre‐eclampsia

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 34 publications
2
64
0
3
Order By: Relevance
“…In this study, we found that heart rate-corrected augmentation index (Alx@75) was higher in pre-eclampsia compared to that in normotensive pregnancy, indicating arterial stiffness. Similar results have been reported by others 41-45…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that heart rate-corrected augmentation index (Alx@75) was higher in pre-eclampsia compared to that in normotensive pregnancy, indicating arterial stiffness. Similar results have been reported by others 41-45…”
Section: Discussionsupporting
confidence: 93%
“…AIx75 and PWV readings, for example, have provided evidence of arterial stiffness at the 11-to 13-week mark in women who subsequently develop preeclampsia. 64 In addition, results of one study found that PWA measured between 11(+0) and 13(+6) weeks of gestation was able to predict 79% of women who developed preeclampsia and 88% of women who developed severe early-onset preeclampsia, with a falsepositive rate of 11%. 65 PWV may be especially useful for predicting preeclampsia in high-risk women.…”
Section: Preeclamptic Pregnancymentioning
confidence: 99%
“…Several studies show increased PWV after clinical onset of PE (1921). More recently, women destined to develop preeclampsia have been shown to have increased PWV as compared to normal pregnancies as early as 11 to 13 weeks gestation (22, 23). Our laboratory has previously reported decreased arterial compliance prior to pregnancy, manifested by increased pulse pressure and pulse wave velocity, in patients who later develop preeclampsia (24).…”
Section: Commentmentioning
confidence: 99%